2008
DOI: 10.1161/circulationaha.108.776203
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of Paroxysmal Atrial Fibrillation and Paroxysmal Atrial Tachycardia in Ambulatory Canines

Abstract: Background-The relationship between autonomic activation and the mechanisms of paroxysmal atrial fibrillation remains unclear. Methods and Results-We implanted a pacemaker and a radio transmitter in 7 dogs (group 1). After baseline recording, we paced the left atrium at 20 Hz for 1 week and then monitored left stellate ganglion nerve activity, left vagal nerve activity, and left atrial electrogram without pacing for 24 hours. This protocol repeated itself until sustained atrial fibrillation (Ͼ48 hours) was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
245
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 283 publications
(259 citation statements)
references
References 32 publications
9
245
0
5
Order By: Relevance
“…8,18,19 Interestingly, studies in lone AF patients and in animal models of both intermittent rapid atrial pacing and congestive heart failure have indicated that AF onset is associated with simultaneous sympathovagal activation rather than with an increase in vagal or sympathetic drive alone. [20][21][22][23] Previously we have shown increased AF susceptibility and AF duration caused by pronounced AERP shortening in a pig model for OSA.…”
Section: Discussionmentioning
confidence: 92%
“…8,18,19 Interestingly, studies in lone AF patients and in animal models of both intermittent rapid atrial pacing and congestive heart failure have indicated that AF onset is associated with simultaneous sympathovagal activation rather than with an increase in vagal or sympathetic drive alone. [20][21][22][23] Previously we have shown increased AF susceptibility and AF duration caused by pronounced AERP shortening in a pig model for OSA.…”
Section: Discussionmentioning
confidence: 92%
“…A 12-month follow-up showed that the 34.4% who appeared the vagal response had a 99% freedom from atrial fibrillation recurrence whereas the other group had an 85% success rate, that is, freedom from recurrence. Scherlag stated that ablation of only the ganglionated plexi in the cadiac fat pads may result in higher success rates and may reduce damage incurred to healthy myocardium.Tan (Tan et al, 2008) further demonstrated that cryoablation of extrinsic sympatho-vagal nerves eliminated paroxysmal atrial fibrillation. These results indicate that rapid ANS modulation does act in the treatment of AF.…”
Section: Review Of Ans Modulationmentioning
confidence: 98%
“…Apesar de resultados controversos na aná-lise da variabilidade da frequência cardíaca no período que precede o início espontâneo de FA, os episódios paroxísti-cos recorrentes parecem estar relacionados com flutuações dinâmicas do tónus autonómico, possivelmente dependendo do sinergismo entre o influxo adrenérgico e a modulação da atividade vagal 5,18,36,37 . São necessários estudos futuros para elucidar o impacto da inervação e da interação da atividade reflexa simpático-vagal na dinâmica complexa do substrato funcional da arritmogénese auricular.…”
Section: Modelos Animais E Estudo Da Vulnerabilidade Para Fibrilhaçãounclassified
“…Foi também demonstrado que a estimulação dos plexus ganglionares cardíacos, que modulam a inervação autonómica, provoca libertação local de neurotransmissores do simpático e parassimpático que podem aumentar o automatismo e encurtar a duração do potencial de ação e refratariedade locais 15 . Recentemente, no modelo do cão, num trabalho com registo direto da atividade autonómica eferente, demonstrou-se que as descargas simultâneas simpático-vagais são frequentemente o fator iniciador de taquicardia auricular paroxística e de FA após um período de pacing auricular esquerdo de alta-frequência 18 . Embora se reconheça que o SNA possa desempenhar um papel importante na fisiopatologia da FA, permanece por esclarecer qual o impacto (isolado ou em combinação) da atividade simpática e/ou vagal na arritmogénese das aurículas e sua implicação na génese, manutenção e interrupção da FA.…”
Section: Introductionunclassified